Algoritma A* Pencocokan Peta untuk Pencarian Tempat Pengelolah Sampah Terdekat - Ramanda, Febri; Sidik Praptomo; M. Ari Prayogo (Prodi Teknologi Informasi Universitas Muhammadiyah Muara Bungo, 2024)
Public waste disposal sites (TPU) are a basic need for the community in managing household waste disposal. In a clean environment, a prerequisite for creating peace of mind, waste management is a problem that makes the environment unclean and beautiful. According to Law No. 18 of 2008, waste management is a systematic, comprehensive and sustainable activity that includes waste reduction and handling. One solution in waste management is a waste bank or public waste disposal site in the city of Muara Bungo which is socialized by the Environmental Service of Bungo Regency regarding environmental problems and city greening programs. TPU services offer services to manage waste and provide waste disposal points, all household waste can be processed properly so that the location of the TPU is known. Determination of a good location point so that consumers feel faster in determining the location of the TP disposal. The data collection method is carried out using the A* algorithm method which is more optimal when compared to Ant Colony, but the map matching method can depict the route into a map. This research is designed to create a shortest route search system with the A* algorithm and map matching, helping people find the shortest route to dispose of household products. The A* algorithm has very easy steps to apply to the system and is fast, from the results of the validation test of the shortest route search for the nearest TPU so that the A* algorithm system can be implemented and become a solution in finding the shortest route.